Discovering the Relevance of Gene Signature of Lung Cancer and Drugs - สุทธหลวง, เตือนจิต; คุรุบรรเจิดจิต, นิลุบล (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2018)
Both nationally and globally, Lung cancer is one of the common and the leading cause of death. The disease is caused by the malfunction of genes in the normal lung cells. Chemotherapy is one type of treatment used to control or inhibit or stop the carcinogenic activity of cancer cells. The relevance of gene signature lung cancer and drug will make it possible to prescribe current medications and discover the new drugs. This article presents how to find gene signatures of lung cancer. Also, how to find drugs that can control gene expression in those lung cancer cells. The purpose of this article is to suggest new drugs of lung cancer that may not have been discovered before. This is the information that the relevant people can take advantage of.